The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/08850666221121593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Awake Prone Positioning in non-Intubated COVID-19 Patients with Acute Hypoxemic Respiratory Failure: A Systematic Review and Meta-Analysis

Abstract: Background Awake prone positioning (APP) has been considered as a feasible treatment for patients with acute hypoxemic respiratory failure in non-intubated coronavirus disease 2019 (COVID-19). However, the efficacy and safety of APP remain uncertain. This meta-analysis aims to assess the effect of APP on intubation rate and mortality in COVID-19 patients with acute respiratory failure. Methods Relevant studies published from January 1, 2020, to June 17, 2022, were systematically searched. The primary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…Our systematic review and meta-analysis con rmed that prone position could signi cantly improve oxygenation in COVID-19 patients with ARDS or AHRF compared with usual care, which is consistent with the results of Fazzini et al 16 . The results also found that prone position can reduce the need for intubation, which is consistent with the results of three recent studies 14,15,38 , but contradicts the results of Fazzini et al 16 , and the reason for this contradiction may be that they have included a large number of observational studies. Our study found no signi cant difference in mortality, hospital LOS, incidence of ICU admission and adverse events between the two groups.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our systematic review and meta-analysis con rmed that prone position could signi cantly improve oxygenation in COVID-19 patients with ARDS or AHRF compared with usual care, which is consistent with the results of Fazzini et al 16 . The results also found that prone position can reduce the need for intubation, which is consistent with the results of three recent studies 14,15,38 , but contradicts the results of Fazzini et al 16 , and the reason for this contradiction may be that they have included a large number of observational studies. Our study found no signi cant difference in mortality, hospital LOS, incidence of ICU admission and adverse events between the two groups.…”
Section: Discussionsupporting
confidence: 87%
“…The effect of prone position may be time-dependent and phase-dependent 47 . The subgroup analysis of Kang et al 15 showed that the intubation rate decreased more signi cantly in the group with longer prone time. Li et al 14 found that prone position has no effect on ICU patients, as prone position is di cult to reduce intubation rate of serious patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, some randomized controlled trials (RCTs) have come to contradictory conclusions in these areas. In the recent three systematic reviews and meta-analyses (16)(17)(18), Li et al reported that the awake prone position can reduce the need for intubation, but have no significant effect on mortality in COVID-19-associated patients with AHRF (16). Kang et al found that the prone position can reduce the intubation rate and mortality of patients (17).…”
Section: Introductionmentioning
confidence: 99%